Enhanced mitigation of fire and explosion risks due to hydrogen leakage using targeted nitrogen nozzle spray approach - Tan, Wei Jian; Ban, Zhen Hong; Chen, Bing Hui; Kim, Kek Seong; Siwayanan, Parthiban; Choong, Thomas S. Y.; Lau, Kok Keong (American Chemical Society, 2022)
Hydrogen leakage may cause destructive incidents due to its high flammability and explosivity. Thus, better preventive methods must be used to mitigate the impacts. This paper proposed an approach using targeted nitrogen nozzle spray to induce both blower ventilation and inert gas atmosphere on leak sources to suppress hydrogen leakage because studies on blower ventilation and inert gas suppression to mitigate hydrogen leakage are usually conducted separately rather than coupled. Its feasibility was studied using computational fluid dynamics. Dispersion of leaked hydrogen, flammability zone, and room temperature were analyzed. Eight cases were conducted to compare three types of nozzle spray orientation, which are horizontal (90°) targeted nozzle spray, slanted (45°) targeted nozzle spray, and overhead sprinkler. The results showed that the slanted (45°) nozzle exhibited better performance. The distance between the nozzle and the leakage point and the nozzle orientations are the deciding factors of equal importance. Shorter distances such as that in targeted sprays can shorten the time for nitrogen to reach the leak source, and more concentrated nitrogen can be presented. However, proper orientation is required to provide better suppression and to prevent further damage. The proposed method can induce blower ventilation and inert atmosphere to suppress the leaked hydrogen effectively. It can be achieved by using existing industrial nozzle, and the hydrogen leakage from different locations can be treated by changing the nozzle orientations.